Monitoring Australian parents' shifting receptiveness to digital mental health interventions during the COVID-19 pandemic. (November 2022) - Linardon, Jake; Westrupp, Elizabeth M; Macdonald, Jacqui A; Mikocka-Walus, Antonina; Stokes, Mark A; Greenwood, Christopher J; Youssef, George J; Teague, Samantha; Hutchinson, Delyse; Sciberras, Emma; Fuller-Tyszkiewicz, Matthew
Background: Nascent evidence indicates that the mental health of parents and children has markedly declined during the COVID-19 pandemic. Considering disruptions to traditional face-to-face mental health services resultant from stay-at-home orders, the potential value of digital mental health interventions has become extremely apparent. Despite this, uptake of digital interventions remains poor, indicating that a better understanding is needed of factors that determine a willingness to use digital platforms. Method: The present multi-wave, longitudinal study of 2365 Australian parents explored between-person and within-person predictors of intentions to use digital interventions during the pandemic. Results: More than one-third of parents reported likely use of a self-guided and therapist-guided digital intervention, with the most endorsed reason for use being to support their child's mental health. Between-person baseline predictors of higher intention ratings were parent's prior mental illness, not living with a partner and recent environmental stressors. Within-person predictors of higher intention ratings were endorsement of mindful parenting strategies, child access to the Internet, better perceived management of child's education, lower social support and financial hardship. Conclusion: Findings demonstrate that willingness to engage in digital interventions fluctuates in response to changing circumstances. Identifying novel ways to increase acceptance and uptake of digital interventions based on modifiable predictors established here is needed to realize the full potential of these modes of care in times of need.